2019
DOI: 10.1161/jaha.118.009146
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptor/Retinoid X Receptor Pathway Plays a Regulatory Role in Pacing‐Induced Cardiomyopathy

Abstract: Background The molecular mechanisms through which high‐demand pacing induce myocardial dysfunction remain unclear. Methods and Results We created atrioventricular block in pigs using dependent right ventricular septal pacing for 6 months. Echocardiography was performed to evaluate dyssynchrony between pacing (n=6) and sham control (n=6) groups. Microarray and enrichment analyses were used to identify differentially expressed genes ( DEG s) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…A more recent study revealed upregulation of the LXR-RXR pathway in samples of human hypertrophic cardiomyopathy, suggesting that LXRs also play an important role in cardiac disease in humans [201]; however, whether this effect contributes to cardioprotection is unknown. Strikingly, a pig model of pacing-induced cardiomyopathy revealed inhibition of the LXR-transcriptional pathway accompanied by increased hypertrophy and fibrosis [202]. This result hints at a complex upstream regulation of LXRs, which may be different in the context of pacing-induced cardiomyopathy.…”
Section: Liver X Receptorsmentioning
confidence: 93%
“…A more recent study revealed upregulation of the LXR-RXR pathway in samples of human hypertrophic cardiomyopathy, suggesting that LXRs also play an important role in cardiac disease in humans [201]; however, whether this effect contributes to cardioprotection is unknown. Strikingly, a pig model of pacing-induced cardiomyopathy revealed inhibition of the LXR-transcriptional pathway accompanied by increased hypertrophy and fibrosis [202]. This result hints at a complex upstream regulation of LXRs, which may be different in the context of pacing-induced cardiomyopathy.…”
Section: Liver X Receptorsmentioning
confidence: 93%
“…Systemic LXR/RXR activation is also important for providing myocardial protection against many diseases, including atherosclerosis, hypertension, and diabetes 77 . Recently, several studies have established that dysregulated LXR/RXR activation was associated with heart disease 78–80 . LXR is activated by oxysterols and there were no oxysterols on our metabolomic panel.…”
Section: Discussionmentioning
confidence: 90%
“…77 Recently, several studies have established that dysregulated LXR/RXR activation was associated with heart disease. [78][79][80] LXR is activated by oxysterols and there were no oxysterols on our metabolomic panel. In this study, proteins related to the LXR/RXR activation pathway had altered levels in Rbp1 -/mice compared to WT mice, in both the left and right ventricles (Table 3).…”
Section: Lxr/rxr Activationmentioning
confidence: 93%
“…The role of PPARα-RXR in regulating the expression of genes related to lipid and energy metabolism in cardiac tissue is well reported in the literature in both cardiac physiology and in pathological conditions (reviewed in [ 26 , 27 ]). On the other hand, the influence of LXR and FXR on cardiac signaling, metabolism and development is not well understood, although studies have related these pathways to cardiovascular pathologies [ 23 , 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%